2012
DOI: 10.7897/2277-4343.03528
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Chemical Variants in Regenerants and Mother Plants of Ashwagandha (W. Somnifera (L) Dunal) by HPTLC Finger Printing

Abstract: HPTLC fingerprints of mother plants and regenerants of W. somnifera (L) Dunal. var JA20, JA134, GLV and wild plants were analysed. Extracts of these drugs were made with three different solvent systems viz. methanol, petroleum ether and chloroform. TLC developed for these extracts prior to perform HPTLC. Toluene, ethyl acetate and formic acid in the ratio (5:5:1) used as the mobile phase. TLC A1 sheets with silica gel 60F254 are used as the stationary phase. HPTLC fingerprints of mother plants and regenerants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this study, variability in phytochemicals was observed at the seedling, vegetative and reproductive stages in the HPTLC profile of leaf and root methanolic extracts. The variation in colours in HPTLC chromatogram bands is attributed to variation in phytochemicals (Shetty and Nareshchandra, 2012) [41] . In the previous HPTLC fingerprinting of methanolic extracts from available capsule made of W. somnifera root has confirmed the presence and absence of phytochemicals, and their concentrations (Nicoletti, 2011) [42] .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, variability in phytochemicals was observed at the seedling, vegetative and reproductive stages in the HPTLC profile of leaf and root methanolic extracts. The variation in colours in HPTLC chromatogram bands is attributed to variation in phytochemicals (Shetty and Nareshchandra, 2012) [41] . In the previous HPTLC fingerprinting of methanolic extracts from available capsule made of W. somnifera root has confirmed the presence and absence of phytochemicals, and their concentrations (Nicoletti, 2011) [42] .…”
Section: Discussionmentioning
confidence: 99%